Glutamate carboxypeptidase II: an overview of structural studies and their importance for structure-based drug design and deciphering the reaction mechanism of the enzyme - Pavlícek, J; Ptácek, J; Barinka, C (Current medicinal chemistry, 2012)
Recent years witnessed rapid expansion of our knowledge about structural features of human glutamate carboxypeptidase II (GCPII). There are over thirty X-ray structures of human GCPII (and of its close ortholog GCPIII) publicly available at present. They include structures of ligand-free wild-type enzymes, complexes of wild-type GCPII/GCPIII with structurally diversified inhibitors as well as complexes of the GCPII(E424A) inactive mutant with several substrates. Combined structural data were instrumental for elucidating the catalytic mechanism of the enzyme. Furthermore the detailed knowledge of the GCPII architecture and protein-inhibitor interactions offers mechanistic insight into structure-activity relationship studies and can be exploited for the rational design of novel GCPII-specific compounds. This review presents a summary of structural information that has been gleaned since 2005, when the first GCPII structures were solved.
Keywords: Crystallography, X-Ray; Humans; Enzyme Inhibitors; Glutamate Carboxypeptidase II; Protein Conformation; zvířata; racionální návrh léčiv; glutamátkarboxypeptidasa II; inhibitory enzymů; polymorfismus genetický; Drug Design; konformace proteinů; Animals; Polymorphism, Genetic; molekulární modely; lidé; Models, Molecular; krystalografie rentgenová